Effectiveness of low-viscosity resin infiltration (Icon) on color change of enamel white spot lesions: 1-year follow-up clinical study - Mohamed. H. Zaazou; Reham S. Saleh; Shahinaz N. Hassan; Ali Abdelnabi; Zeinab M. Zaki; Tamer M. Hamdy; Dalia Y. Zaki; Lamiaa M. Moharam (Bulletin of the National Research Centre, 2024)
Abstract Background To evaluate the effect of the low-viscosity Icon resin infiltrate application on the color change of white spot enamel lesions (WSLs) over 3-, 6-, and 12-m follow-up periods. Methods Ninety-six teeth diagnosis with WSLs using the ICDAS scoring system in 49 participants were assessed for their color change using the Icon resin infiltration technique. The Icon kit was applied to WSLs as instructed by the manufacturer. Icon-Etch (15% hydrofluoric acid) was applied to the lesions for 2 min, and then, it was rinsed off with copious amount of water for 30 s. Then, Icon-Dry (99% ethanol) was applied to the etched lesions for 30-s followed by the application of the Icon resin infiltrate that was light cured for 40 s. Color change assessment was performed using Vita Easyshade V spectrophotometer at baseline and immediately after Icon resin infiltration, then at 3-, 6-, and 12-m follow-up periods. Analysis of the data was performed using the test of repeated measure ANOVA and the paired sample t test. Results There was a statistically significant difference in ∆E between the different follow-up periods at immediate, 3-m, 6-m, and 12-m. The highest mean value was found in the immediate follow-up period, while the lowest mean value was found in 12-m follow-up period. Conclusions Low-viscosity Icon resin infiltration has the ability for immediate diffusion into the WSLs giving an immediate improvement in the esthetic outcome of the WSLs. However, its long-term outcomes might not be consistent for the color change of the WSLs.